Networked Identities: Exploring the Role of Social Networking to Optimize Event Marketing by Higher Education Institutions in the Middle East. (December 2020) - Asim, Mian Muhammad; Rasul, Azmat
This article examines the growing use and influence of two popular social networking sites—Facebook and LinkedIn—in the Middle East. Under the premise of Social Identity theory, we focus on the impact of posting information about academic-related events on social networking sites. We recruited 180 participants in a laboratory-based experiment using a 2 (medium type) × 2 (message valance) × 2 (group affiliation) factorial design to assess the moderating role of medium credibility, electronic word-of-mouth valence (eWOM) and perceived in-group affiliation of the respondents. The results indicate that, under the same moderating conditions, popular and widely used social sites are more capable of generating a positive response from students than sites that are not popular or widely used. In addition, the theoretical and practical implications of the findings are addressed.